The Japanese judo training process from a perspective related to long-term athlete development - Junior, A. C. T.; da Silva, L. H.; Pimenta, T. F. d. F.; Dos-Santos, J. W. (International Journal of Sports Science & Coaching, 2025)
The study aims to describe the organizational and methodological aspects of Japanese judo in its various stages of preparation and verify their relationship with the principles of Long-Term Athlete Development. This data originated from the analysis of the author's material obtained during the exchange program "Discovery Camp: Tomorrow's Friends Programme Judo for School PE 2019." The manuscript has an observational design with a descriptive profile and a qualitative approach through a case study. Based on the observations that the exchange provided, the results indicate a convergence between the methodology and organization of Japanese judo and the proposals of Long-Term Athlete Development. Above all, this convergence pertains to the content and objectives of each phase, as well as the transitions between the various preparation periods, which include adaptations to competition rules and the gradual physical, technical, and tactical development of judokas, without concern for the immediacy of results. The methodology applied in the preparation process of Japanese judo can be divided into periods: Sports Initiation, which advocates acquiring a wide range of motor skills; Initial Specialization, progressing to a wide variety of skills specific to judo; the Specialization phase, during which there is significant technical and tactical deepening along with the improvement of physical capacities necessary for performance; and the high-performance phase, focusing on competitive results.